A mediação como dispositivo de política cultural - quatro experiências que repensam a prática teatral como ação comunicativa - Perez, Shirlei Torres (2012)
This MA dissertation aims to provide a new meaning to the concept of mediation as applied to cultural policies. This new meaning stems from Jesús Martin-Barbero s ideas in the field of communication. In arts and drama in particular the word mediation refers to an action whereby one intermediates a dialogue between the audience and artists, or between curators and spectators. Some professionals from cultural centers are commonly referred to as cultural mediators. However, as we provide a new meaning to mediation by defining it as sign mediation, these relationships are no longer placed in opposite extremes as suggested by such phrases as passive/active, wise/ignorant, genial artist/common man. As we set some strategies to approach theatrical experience to communication, we will face some issues that provide visibility to a complex information network. This network does not refer solely to creative processes, but also encompasses production, media, and product and process flowing. The research corpus is comprised by experiences reported by the groups El Periférico de Objetos (Argentina), Compagnie Dakar (the Netherlands) and Théâtre du Soleil (France), as well as the play Caramelo de Limón (Argentina). In addition to Martin-Barnero (2003), the theoretical grounds of this paper lie on the works by Lucrecia D Alessio Ferrara (2008), Boaventura de Souza Santos (2010), Lipovetsky (2010), and Greiner (2010). These authors made it possible to design a new critical vision on creating new arrangements, the ecology of knowledge and the notion of world-culture among other corelated issues. As a result, we open the pathway to redefining some possible action plans in the field of art and culture, thus providing an effective proposal for one s education and political activation. Current action plans require extreme changes in their review parameters not only in large cities such as São Paulo, but also in decentralized circuits which are still regarded within a peripheral framework of knowledge